2002
DOI: 10.1034/j.1399-5618.2002.01189.x
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate versus Bupropion SR when added to mood stabilizer therapy for the depressive phase of bipolar disorder: a preliminary single‐blind study

Abstract: These preliminary data suggest that adjunctive topiramate may reduce depressive symptom severity in acute bipolar depression. The antidepressant efficacy of this compound requires confirmation via double-blind placebo controlled investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(82 citation statements)
references
References 31 publications
2
78
0
2
Order By: Relevance
“…[63][64][65][66] Rigorously performed, controlled trials, however, failed to find any benefit from use of this drug in bipolar disorder. 67 Topiramate has been commonly prescribed for patients with bipolar disorder, not only because of the expectation that it will prove to be efficacious, but also because of its weight-reducing effects, which are felt to be particularly desirable to counteract the weight gain induced by some other mood stabilizing agents (e.g., valproic acid).…”
Section: Topiramatementioning
confidence: 99%
“…[63][64][65][66] Rigorously performed, controlled trials, however, failed to find any benefit from use of this drug in bipolar disorder. 67 Topiramate has been commonly prescribed for patients with bipolar disorder, not only because of the expectation that it will prove to be efficacious, but also because of its weight-reducing effects, which are felt to be particularly desirable to counteract the weight gain induced by some other mood stabilizing agents (e.g., valproic acid).…”
Section: Topiramatementioning
confidence: 99%
“…Topiramate has demonstrated substantial beneficial effects in the treatment of bipolar disorder in open-label trials (Marcotte, 1998;Chengappa et al, 1999;McElroy et al, 2000;Chengappa et al, 2001a;Guille and Sachs, 2002;McIntyre et al, 2002;Vieta et al, 2002). Phase III trials of topiramate as monotherapy for acute bipolar mania, did not demonstrate a statistically significant advantage over placebo, although all studies demonstrated significant weight loss (Data on file, 2003).…”
Section: Newer Treatments For Bipolar Disordermentioning
confidence: 99%
“…Estudos abertos sobre os efeitos do topiramato no tratamento de episódios de mania, mistos e de depressão do TB sugeriram um possível benefício em casos de má resposta aos tratamentos (Hussain et al, 2001;McIntyre et al, 2002). O estudo de McIntyre et al (2002), inclusive, que comparou o topiramato e a bupropiona, com desenho simples-cego (n = 36), não evidenciou diferenças significativas em relação à eficácia nos dois grupos.…”
Section: Topiramatounclassified
“…O estudo de McIntyre et al (2002), inclusive, que comparou o topiramato e a bupropiona, com desenho simples-cego (n = 36), não evidenciou diferenças significativas em relação à eficácia nos dois grupos. São necessários, contudo, estudos duploscegos controlados para a melhor avaliação dos benefí-cios do topiramato no tratamento da depressão bipolar.…”
Section: Topiramatounclassified